Using the Enhanced Critical Incident Technique in Counselling Psychology Research - Butterfield, Lee D.; Maglio, Asa-Sophia T.; Borgen, William A.; Amundson, Norman E. (Canadian Journal of Counselling and Psychotherapy, 2009)
This article describes an effective approach to using the Enhanced Critical Incident Technique (ECIT) research method based on Flanagan’s (1954) Critical Incident Technique (CIT). It begins with an overview of the CIT, how to decide if it is the appropriate methodology to use, then using a recent CIT study as an example discusses Flanagan’s five steps for conducting a CIT study: determining the activity’s aim; setting plans, specifications, and criteria for the information to be obtained; collecting data; analyzing the data; and reporting the findings. Nine credibility checks, developed to increase the rigor and credibility of the ECIT, are described.